RESISTIVITY OF LATTICE VACANCIES IN STAINLESS STEEL 316 - Rana, Anwar Manzoor; Khan, Abdul Faheem; Abbas, Amer; Ansari, M. Iqbal; Bhatti, M. Tariq (Journal of Research (Science), 2001)
Specimens of SS316 were solution treated for 60 min. at different temperatures i.e. 800 and 900°C, quenched in brine and aged at 70 and 450°C for various times. Cold worked specimens (75% cold rolled) were annealed at 40 and 70°C for different times. It is observed that resistivity first rises and then falls after subsequent annealing or aging at a constant temperature. The increase in resistivity after quenching and cold working is found to be due to creation of defects and imperfections such as vacancies and dislocations. The annealing can be attributed to recovery and recrystallization processes. The initial increase in resistivity during aging may be described by the formation of clusters/ precipitates at early stages of precipitation.